Exploring assessment reform in Malaysian primary schools - Shanusi Ahmad (2022)
This study aims to explore the implementation of assessment reform initiatives known as the National Education Assessment System (NEAS) from the perspectives of school adminstrators and teachers and in two primary schools. The objectives of the study were: (a) to explore the approaches developed by schools in response to NEAS, (b) to explore the factors which affect the implementation of NEAS, and (c) to identify the factors in schools which impact upon the implementation of NEAS. The main model used in this study was Concern-Based Adoption Model (CBAM). This model explained about the teachers concern within a context of assessment reform. This study used a qualitative case study which involved 8 informants from two primary schools. Semi-structure interview protocol and document analysis were the insruments used to collect qualitative data. Qualitative data analysis using thematic analysis was also utilised in this study. The supportive result shows that the relationship among the teachers, management team, students, parents and community are crucial to facilitate the implementation of the NEAS. In addition, teachers beliefs, leadership quality, and school culture were also critical elements. However, the suppressive factors for NEAS implementation such as low teachers morale and negative students attitude were the emerging themes from the study. In other words, there is a need to improve not only the system but also the delivery of the NEAS. In conclusion, the study found that the critical factors such as school leaderships support, teachers beliefs and training are pertinent to facilitate the implementation of NEAS. In implication, the framework developed by this study can be used by the Malaysian Examination Syndicate, school administrators, and teachers to revamp or redesign the current NEAS implementation.